The NBC Defence Troops Specialists` Expedition to Matua Island in the Kuril Chain - S. V. Kuzhelko; V. A. Kovtun; D. P. Kolesnikov (Вестник войск РХБ защиты)
In May 2016 a special expedition by Russia’s Defence Ministry and Russian Geographical Society was organized in order to explore the island of Matua located near the centre of the Kuril Islands chain. By the beginning of World War II the island has been turned into the veritable fortress by the Japanese. There were certain reasons to suggest that the island could be used by the Japanese military for the development, production and stockpiling of weapons of mass destruction. Because of that an NBC control group, formed from the specialists of several scientific research institutions of the Radiological, Chemical and Biological Defence Troops of the Armed Forces of the Russian Federation was included in the joint team. The tasks of the group were to reveal and evaluate the NBC environment on Matua Island, to provide the protection of the personnel and the mitigation of any possible NBC contamination of the terrain and the Japanese military installations on the island. The group was also supposed to check the operational characteristics of NBC reconnaissance equipment and to conduct biological analysis at high northern latitudes without any fixed-site laboratories. The expedition has been working on the island from April 20 until June 29, 2016. The survey of the fortifications and engineering constructions on Matua Island, as well as the analysis of the contents of several chemical tanks and bottles, found on the island, revealed the absence of any evidence of the production of chemical, biological and nuclear weapons on Matua at the time of the Japanese military presence until August 1945. The analysis of the environmental samples (soil and water), taken at the locations of the surveys, and of the biological samples, taken from the organs of several mouse-like rodents, caught near the expedition camp, did not reveal any causative agents of infectious and particularly dangerous diseases. The radioactive contamination, residual radiation and gamma-rays were not detected on the territory of the island.